The Effectiveness of Prezi Video Media in Developing Religious and Moral Values Among Early Childhood Learners - Datubua Toboe, Trivena; Nurhayati, Nurhayati; Putri Setianingsi, Hesti; Agusniatih, Andi (Universitas Islam negeri Mahmud Yunus Batusangkar, 2025)
The development of religious and moral values is a crucial foundation in shaping the character of early childhood learners. This study aims to evaluate the effectiveness of Prezi Video media in fostering religious and moral development in Group B children. Employing an experimental design with a quantitative approach, the study focused on three core aspects: identifying religions and places of worship, maintaining personal hygiene, and performing prayers according to one's faith. A total of 15 children from Tut Wuri Handayani Kindergarten participated in the study. Data were collected through pre-test and post-test observations conducted before and after the implementation of Prezi Video media. The findings revealed a significant improvement across all three aspects, with most children progressing from the